Characterising a homozygous two‐exon deletion in UQCRH: comparing human and mouse phenotypes. Issue 12 (8th November 2021) - Vidali, Silvia; Gerlini, Raffaele; Thompson, Kyle; Urquhart, Jill E; Meisterknecht, Jana; Aguilar‐Pimentel, Juan Antonio; Amarie, Oana V; Becker, Lore; Breen, Catherine; Calzada‐Wack, Julia; Chhabra, Nirav F; Cho, Yi‐Li; et al.
Abstract: Mitochondrial disorders are clinically and genetically diverse, with isolated complex III (CIII) deficiency being relatively rare. Here, we describe two affected cousins, presenting with recurrent episodes of severe lactic acidosis, hyperammonaemia, hypoglycaemia and encephalopathy. Genetic investigations in both cases identified a homozygous deletion of exons 2 and 3 of UQCRH, which encodes a structural complex III (CIII) subunit. We generated a mouse model with the equivalent homozygous Uqcrh deletion ( Uqcrh −/− ), which also presented with lactic acidosis and hyperammonaemia, but had a more severe, non‐episodic phenotype, resulting in failure to thrive and early death. The biochemical phenotypes observed in patient and Uqcrh −/− mouse tissues were remarkably similar, displaying impaired CIII activity, decreased molecular weight of fully assembled holoenzyme and an increase of an unexpected large supercomplex (SXL ), comprising mostly of one complex I (CI) dimer and one CIII dimer. This phenotypic similarity along with lentiviral rescue experiments in patient fibroblasts verifies the pathogenicity of the shared genetic defect, demonstrating that the Uqcrh −/− mouse is a valuable model for future studies of human CIII deficiency. SYNOPSIS: This work describes the first confirmed pathogenic variant in UQCRH in two children presenting with recurrent episodes of metabolic crisis. A mouse model harbouring the equivalent variant in Uqcrh shared similar biochemical phenotypes of impaired CIII activity and abnormal OXPHOS supercomplex structures, but with more severe manifestation. A 2.2 kb homozygous deletion of exons 2 and 3 of UQCRH (chr1:g.46, 774, 245‐46, 776, 461) was identified through WES in two cousins that presented with episodes of lactic acidosis, hyperammonaemia and impaired glucose homeostasis. A viable mouse model carrying the equivalent two‐exon deletion in Uqcrh was generated and systematically phenotyped, displaying important characteristics of human CIII disorders. CIII activity and assembly in both patient fibroblasts and Uqcrh −/− mice were impaired by Uqcrh/UQCRH absence. Its lack of expression, however, still allows dimerisation. Aberrant assemblies of respiratory supercomplexes including an increase of a large supercomplex (SXL) were revealed by complexome profiling in both patient fibroblasts and Uqcrh −/− mouse tissue. Abstract : This work describes the first confirmed pathogenic variant in UQCRH in two children presenting with recurrent episodes of metabolic crisis. A mouse model harbouring the equivalent variant in Uqcrh shared similar biochemical phenotypes of impaired CIII activity and abnormal OXPHOS supercomplex structures, but with more severe manifestation.